Chapter Historia literaria en la edad global: una lectura crítica desde América Latina - Loy, Benjamin (De Gruyter, 2018)
The two volumes gather the most important findings of the nine sessions held at the AIH conference in Münster, Germany, in 2016. The contributions focus on current research trends in Spanish literary studies, cultural studies, and linguistics. Central topics include transitions (in 18th- and 19th-century literature), crises and disruptions (in contemporary literature), transculturations and transitory identities (in view of Latin America).